KUALITAS LAYANAN INTERNET BANKING DAN KARAKTERISTIKNYA BERDASARKAN FREKUENSI PENGGUNAAN - Mujilan, Agus (Widya Warta, 2013)
This study reexaminesthe dimensions of Internet Banking (IB) Service Quality bythe Indonesian internet users.It analyses the impact of the frequency of IB use toward IB users’ quality perception. The internet userswere categorized into two types: IB users and non-users. An online and post mail surveyswere conducted to collect the data. The respondents were internet usersfrom: undergraduate accounting lecturers of Indonesian Catholic Universities, accounting staffs of private companies, email users, facebook users, and tokobagus users. The result indicates not all of the quality dimensions are significant. There is a different perception of IB users and non-users.Only assurance is significant for both users and non-users. The frequency of IB usealso makesa different perception on quality dimension. This study also shows that there is a different quality perception between countries. It means that studying internet banking quality or offering the internet banking serviceto customers must consider the characteristics of internet users in each area.